Overview of controlling concepts - Аssilova, A.S.; Mussabekova, A.N. (BUKETOV BUSINESS REVIEW, 2018)
This article summarizes the theoretical concepts of controlling. As practice shows, strategically oriented management requires comprehensive information, analytical, organizational and methodological support, which cannot be fully ensured in the framework of management accounting and control. Controlling must satisfy this need, which represents an effective form of support for management functions. The emergence and evolution of controlling as a tool for managing a company are due to the development and complication of the structure of market relations that change the internal and external environment, so controlling became the result of the formation of a new concept of business management. The content of the definition of controlling foreign and domestic economists is disclosed. Two types of controlling, operational and strategic, are described, and the main objectives, functions and tasks of controlling are substantiated. Controlling as a system in the management of an enterprise was considered and its main subsystems were identified. The basic concepts of controlling and their essence and tasks are shown. The content of modern methods of controlling is disclosed. The role of controlling in the Republic of Kazakhstan on the example of a large company is considered. It is concluded that the controlling system creates certain advantages for enterprises and affects the socio-economic development of the country as a whole